2002
DOI: 10.1248/cpb.50.1007
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenicity of Steviol and Its Oxidative Derivatives in Salmonella typhimurium TM677.

Abstract: Stevioside1) is natural non-caloric sweetener from Stevia rebaudiana BERTONI, which has been used for a long time in Paraguay and Brazil. Purified stevioside is an odorless powder approximately 250 to 300-fold sweeter than sucrose, and is composed of steviol, a diterpenic hydroxy carboxylic acid and three glucose molecules. At present, stevioside is widely used as a non-caloric sugar substitute, and in various kinds of drinks and food products in many countries. In Japan alone, approximately 200 t of S. rebaud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 12 publications
1
25
0
2
Order By: Relevance
“…However, stevioside and even steviol were inactive in various other TA strains of Salmonella typhimurium with or without S9 mix at doses up to 5 mg/plate (TA 97, 98, 100, 102 and 104), in Escherichia coli WP2 wv/vl/pKMlOl and in the rec-assay using Bacillus subtilis even when activation S9 mix was present (99% purity, 13; 96% purity, 14). The direct mutagenic activity of 15-oxo-steviol was refuted by (19), but confirmed by (17). The activity of steviol in Salmonella typhimurium TM677 was very low and was only about 1/3000 that of 3,4-benzopyrene and that of steviol methyl ester 8,13 lactone was 1/24500 that of furylfuramide (17).…”
Section: Steviolmentioning
confidence: 98%
See 2 more Smart Citations
“…However, stevioside and even steviol were inactive in various other TA strains of Salmonella typhimurium with or without S9 mix at doses up to 5 mg/plate (TA 97, 98, 100, 102 and 104), in Escherichia coli WP2 wv/vl/pKMlOl and in the rec-assay using Bacillus subtilis even when activation S9 mix was present (99% purity, 13; 96% purity, 14). The direct mutagenic activity of 15-oxo-steviol was refuted by (19), but confirmed by (17). The activity of steviol in Salmonella typhimurium TM677 was very low and was only about 1/3000 that of 3,4-benzopyrene and that of steviol methyl ester 8,13 lactone was 1/24500 that of furylfuramide (17).…”
Section: Steviolmentioning
confidence: 98%
“…The direct mutagenic activity of 15-oxo-steviol was refuted by (19), but confirmed by (17). The activity of steviol in Salmonella typhimurium TM677 was very low and was only about 1/3000 that of 3,4-benzopyrene and that of steviol methyl ester 8,13 lactone was 1/24500 that of furylfuramide (17). Although a weak activity of steviol and some of its derivatives was found in the very sensitive S. typhimurium TM677 strain, the authors concluded that the daily use of stevioside as a sweetener is safe.…”
Section: Steviolmentioning
confidence: 99%
See 1 more Smart Citation
“…Bij gebruik als zoetstof zijn geen nadelige effecten op de voortplanting beschreven, noch teratogene, carcinogene of allergische effecten (Geuns, 2003;EFSA 2010). In in vitro-onderzoek is een genotoxisch effect beschreven van steviol en enkele van diens metabolieten in een zogenoemde voorwaartse mutatie-assay in Salmonella typhimurium TM677 (Pezzuto et al, 1985;Terai et al, 2002). Dit effect lijkt zich echter niet zonder meer naar de in vivo-situatie te vertalen: slechts 1 onderzoek heeft een in vivo genotoxisch effect beschreven bij dieren met behulp van een zogenoemde 'komeettest' (Nunes et al, 2007).…”
Section: Metabolisatie En Toxicologieunclassified
“…Teniendo en cuenta que preocupaciones de genotoxicidad relacionados con la ingesta de steviol glucósidos, tienden a perpetuarse en la literatura, realizaron: (1) revisión de los estudios de genotoxicidad que constituyen fuentes de incertidumbre, (2) revisión adicional de estudios publicados desde 2008, que pueden dilucidar un potencial de genotoxicidad en seres humanos, y (3) evaluación de la necesidad de realizar estudios adicionales de genotoxicidad in vivo. Terai et al (2002) sostienen TM677 posee alta especificidad, y en este sentido no es apropiada para la evaluación de la seguridad de salud humana. Asimismo Brusick (2008) ha sostenido que la dosis de steviol, produce citotoxicidad excesiva (aproximadamente 100% en el gen de ensayo de mutación y >50% de muerte celular en el ensayo de aberración cromosómica).…”
Section: Introductionunclassified